2021
DOI: 10.7759/cureus.16142
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Central Retinal Artery Occlusion by Point-of-Care Ultrasound in the Emergency Department: A Case Series

Abstract: Central retinal artery occlusion (CRAO) is a rare, but serious, diagnosis that can lead to blindness, most often due to thromboembolic disease. In the emergency department (ED), CRAO can present as acute, painless loss of vision. Physicians need quick ways to rule in this diagnosis due to the time-sensitive nature of the event. We describe two patients in this cases series who present to the same ED with unilateral painless vision loss and histories that include notable risk factors such as thromboembolic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…Since review articles with information on practical ultrasound applications in diagnosing retinal ischemia are lacking ( 7 , 14 , 16 ), we agree with the other authors that the message regarding the possible practical utility of Neuro-POCUS in diagnosing CRAO requires wider dissemination ( 64 ). Furthermore, one in three ophthalmologists reported that they would not transfer their patients with CRAO to a stroke center ( 21 ), thus leaving the patients at risk of future stroke or other cardiovascular conditions.…”
Section: Neurosonologist’s Perspective On Retinal Strokesupporting
confidence: 61%
“…Since review articles with information on practical ultrasound applications in diagnosing retinal ischemia are lacking ( 7 , 14 , 16 ), we agree with the other authors that the message regarding the possible practical utility of Neuro-POCUS in diagnosing CRAO requires wider dissemination ( 64 ). Furthermore, one in three ophthalmologists reported that they would not transfer their patients with CRAO to a stroke center ( 21 ), thus leaving the patients at risk of future stroke or other cardiovascular conditions.…”
Section: Neurosonologist’s Perspective On Retinal Strokesupporting
confidence: 61%
“…This classic presentation should immediately raise suspicion of an acute stroke and therefore prompt rapid diagnosis, workup, and treatment. Unfortunately, there is often a delay in diagnosis secondary to patients' time of presentation and challenges with obtaining appropriate ophthalmic funduscopic evaluation emergently [5]. Point of care ultrasound may be of greater utility in aiding the diagnosis, especially in a setting where access to emergent ophthalmic care and evaluation is limited [6].…”
Section: Discussionmentioning
confidence: 99%